Спонтанна флора Національного ботанічного саду імені М.М. Гришка НАН України (м. Київ). Повідомлення 2. Методологічні проблеми і критерії виділення адвентивних ергазіофітів в умовах інтродукційного осередку - Shynder, O.I. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2019)
Objective – to develop and implement criteria for the selection of escaped plants on the example of spontaneous flora of M.M. Gryshko National Botanical Garden of the NAS of Ukraine (Kyiv). Material and methods. The object of the study is the taxonomic composition of the spontaneous flora of the M.M. Gryshko National Botanical Garden of the NAS of Ukraine. The research was conducted in 2010–2018 on the territory of the Botanical Garden. Results. The definition of the term “escaped plants” in different sources is considered. The stage of the output of alien taxa outside the culture (sintering) in different classification scales of the process of acclimatization is analyzed. For the study of escaped plants in the spontaneous flora of the Botanical garden, a criterion for their selection was formulated. Examples of different groups of escaped plants in the spontaneous flora of M.M. Gryshko National Botanical Garden of the NAS of Ukraine are given. Conclusions. In the easteuropean scientific literature the term “ergasiophytes” has become much wider than it in the primary source and is now mainly used for the definition of “escaped plants”. Within the spontaneous flora of “escaped plants”, synonymously are “runaways from culture”, and within the cultural flora are close to “introducents”. Until now, there are no unified methodological principles for conducting an escaped plants inventory in botanical gardens. The boundaries of their “out of the culture” have not been clearly defined. We have formulated the main criterion for the selection of “escaped plants”: the fixation of adult individuals of the taxa in two or more spontaneous locations outside the cultivation area and preferably not in the vicinity of it. This criterion was tested on the example of the spontaneous flora of M.M. Gryshko National Botanical Garden of the NAS of Ukraine.